The Inorganic Radiochemistry of heavy elements - Zvára, Ivo (H: Springer, 2017)
Volatility of elements and compounds has been occasionally used forradiochemical separations since the studies of Mme. Curie. Steady progress in nuclear sciences and technologies posed new problems in separation of mixtures of radionuclides. In the 1960s radiochemists paid attention to numerous volatile halides and oxyhalides of metallic elements. These compounds then helped in dis- covery and studies of the first, short-lived transactinoid elements. Needs of this par-ticular field continue to motivate and stimulate further development. In this book,the author will attempt a coherent look on the physicochemical background of all steps involved in the experiments. The emphasis will be on gas-solid chromatogra-phy, which provides the required data on volatile compounds. So far, conventional interpretation of the adsorption data in terms of thermodynamic characteristics has ignored heterogeneity of real column surfaces and their modification by the em-ployed gaseous reagents. It necessitates a major revision of some conclusions from past studies. The Introduction, besides others, specifies some terms used in the book, especially in view of the problems of single atom chemistry. A schematic illustrates the place of the heaviest elements in the Periodic Table and the classes of volatile species, which are used for their chemical identification and further characterization.A radiochemical experiment involves two principal steps. The first is obtaining the desired compound. Second, generally, is isolation of the compound. It may meanthe isolation from a bulk matrix, separation of a complex mixture of radionuclides, or both. The separations are behind both applied and fundamental radiochemistry studies, which is the major emphasis in this book. Already in the early days of radiochemistry some radionuclides were isolated from matrices and their mixtures were separated, making use of different volatility of various elements and compounds. Well-known is the role of the extreme volatil-ity of radon in the discovery of “emanations” by Dorn and Rutherford (see a de-tailed story in Reference [1]). In her logbooks Mme. Curie noted purification of polonium by sublimation, when collecting deposits obtained at different tempera-tures [2]. After the discovery of nuclear fission, the volatile species — Kr and Xe in the elemental state, As and Sb as gaseous AsH3 and SbH 3,aswellasRuinthe xix xx Introduction state of RuO4— were often used for isolating these elements from mixed fission products. It was noted that the separations can be made quickly. Such early works were covered in review papers and reports [3–5].In the beginning of the 1960s, Merinis and Boussieres [6] faced the task of separating products of spallation reactions. They pioneered the gas-phase separa-tions of transition metals that are capable of forming highly to moderately volatile higher (oxy)halides. Successful employment of such an abundant class of com-pounds, albeit easily hydrolyzable, was an important achievement. These authors also introduced a novel variant of gas-solid chromatography — the thermochro-matography, which is carried out in columns with downstream negative temperature gradient. The gaseous species of different adsorbability get practically irreversibly deposited in different temperature ranges along the column, thus yielding a prepara-tive chromatogram. The latter possibility is an advantageous feature for application in radiochemistry: the isothermal elution gas chromatography, even though provid-ing better resolution, requires much more time and rather sophisticated techniques for collecting the separated fractions, and for subsequent radiation measurement. Soon after, various authors occasionally employedthermochromatography to sepa-rate some fission products, both metals and nonmetals, as chlorides. All these exper-iments dealt with mixtures of relatively long-lived activities and were done by batch processing. Fast performance or high chemical yield was not of major concern. In the mid-1960s, making use of volatile compounds and of gas chromatographic techniques, the present author with co-workers at JINR, Dubna first solved a new, most difficult radiochemical problem — “on-line” chemical identification and fur-ther studies of transactinoids, the elements with atomic numbers larger than 103.The latter can be produced only at accelerators of “heavy ions” (particles heavier than He) by the bombardment of mostly radioactive actinoid targets.They are ob-tained as single and very short-lived atoms — on the “one-atom-at-a-time” scale.The solution was found by combining the following principles: •The use of “thin” solid targets for prompt extraction of the bombardment prod-ucts owing to their recoil energy •Thermalizing the recoils in a gas flowing through the “target chamber” to enable their fast interaction with gaseous reagents •Feeding the necessary gaseous reagents into the target chamber or next to its exit to realize in situ “chemical volatilization” •The use of the beneficial properties of gases for rapid transportation of thevolatile species to a separation equipment and radiation detectors •Isolation of the new element by a gas-solid chromatography technique The JINR group had been alone in the field of gas-phase chemistry of transacti-noid elements until the 1990s. From the very beginning they felt it necessary to provide at least limited physicochemical background for the initially empirical con-clusions. Otherwise, one could not be sure that the regularities disclosed in the test runs would also be valid for yet unknown elements. One of the goals of this book is to survey, generalize and discuss the present knowledge, as well as ignorance, about the fundamentals of the gas-phase techniques, which are used in inorganic